Development of Software that Supports the Improvement of Mathematical Skills in Children - Rodríguez Aguiñaga, Adrián; Quezada, Angeles; Ramírez Ramírez, Margarita; Calvillo Tellez, Andres (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Several applications have currently been developed to assist children in learning mathematics. However, many of these applications were created in different languages or designed for distinct social contexts, and some are now outdated. Given the factors mentioned above, a mobile application was created to help children develop mathematical skills. Through expert testing, an application was developed that meets both content and usability standards, ensuring that users feel comfortable while using it. The software was validated through multiple tests, yielding promising results.